WILLINGNESS TO EMBED SOCIAL SUSTAINABILITY: A CASE OF GEN Y AND GEN Z ENTREPRENEURS IN INDONESIA - Sherlywati Sherlywati; Eliot Simangunsong (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2023)
This research aimed to explore the motivators and willingness of Gen Y and Gen Z entrepreneurs in Indonesia to embed social sustainability in their businesses. This research employed a quantitative method via an online survey questionnaire, which was conducted based on a convenience sample of Gen Y and Gen Z alumni and students from several universities in Indonesia. The data were processed using SEM-SmartPLS3.0. The research finding showed that instrumental and normative motivators affected the willingness to embed social sustainability, while relational motivators had no effect. Previously, social sustainability research involved established industries and companies. However, this research focused on upcoming Gen Y and Gen Z entrepreneurs. The recommendations provided by this research for developing a sustainable business strategy framework in terms of social dimension for Gen Y and Gen Z entrepreneurs, among others, include strengthening the indicators of normative and instrumental motivators, and the willingness to embed social sustainability.